Austin and His Friends - Balfour, Frederic Henry, 1846-1909 (Salt Lake City, UT : Project Gutenberg, 2005)
"Austin and His Friends" by Frederic Henry Balfour is a novel written in the early 20th century. The story centers around a young boy named Austin Trevor, who becomes a cripple after losing a leg due to a medical condition. Despite his physical challenges, Austin maintains a positive outlook on life, filled with imaginative thoughts and a deep appreciation for nature and art. The novel presents a light-hearted approach to the ghost story genre, showcasing Austin's unique perspective on life and the people around him. The opening portion of the book introduces the reader to Austin's life and circumstances. Described vividly, Austin's home is depicted as a serene and comforting environment where he has grown up. Following a life-altering surgery that results in him losing his leg, Austin must adapt to his new condition, but instead of sinking into despair, he finds beauty in his surroundings and even in his new wooden leg. The text emphasizes his philosophical musings and the affectionate yet humorous interactions with his Aunt Charlotte, who struggles to understand his approach to life. In this section, we glimpse Austin's determination to embrace life with joy and humor, setting the tone for his adventures and explorations ahead. (This is an automatically generated summary.)
Release date is 2005-06-21
E-text prepared by Marilynda Fraser-Cunliffe, Jeannie Howse, and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: People with disabilities -- Fiction; Young men -- Fiction; Aunts -- Fiction; Apparitions -- Fiction